2021
DOI: 10.1038/s41467-021-22354-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration in middle and old age with incidence of dementia

Abstract: Sleep dysregulation is a feature of dementia but it remains unclear whether sleep duration prior to old age is associated with dementia incidence. Using data from 7959 participants of the Whitehall II study, we examined the association between sleep duration and incidence of dementia (521 diagnosed cases) using a 25-year follow-up. Here we report higher dementia risk associated with a sleep duration of six hours or less at age 50 and 60, compared with a normal (7 h) sleep duration, although this was imprecisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
221
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(244 citation statements)
references
References 52 publications
16
221
4
3
Order By: Relevance
“…Researchers recently analyzed 25 years of health data from nearly 8,000 middleaged people and found a link between sleep and dementia as people get older. Middle-aged people with long-term sleep less than or equal to 6 h have a 30% increased risk of dementia (Sabia et al, 2021). However, the current research on how sleep loss promote the occurrence of dementia is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers recently analyzed 25 years of health data from nearly 8,000 middleaged people and found a link between sleep and dementia as people get older. Middle-aged people with long-term sleep less than or equal to 6 h have a 30% increased risk of dementia (Sabia et al, 2021). However, the current research on how sleep loss promote the occurrence of dementia is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…These studies and our findings indicate that, despite the undecided temporality of SMI and depressive symptoms, the presence or absence of depressive symptoms is the most significant variable differentiating older adults with or without SMI. Given that SMI [1,7,80] and depressive symptoms [81,82] are independent risk factors for MCI or Alzheimer's disease and that depressive symptoms and SMI are more prevalent generally among racial and ethnic minority elders [17,65,[83][84][85][86][87][88], the prevention and treatment of depression among racial and ethnic minority elders are critical for the prevention of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…For the interaction analysis, depressive symptom scores were categorized into minimal (0–4), mild (5–9), and moderate/severe (10 or higher), and sleep hours were divided into two categories (less than 6 h and 6 or more hours). The literature suggests that a sleep duration of 6 h or less is associated with an increased incidence of dementia later in life [ 65 ]. SPSS version 25 was used to conduct all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Short sleeping time is often associated with impaired performance in memory tasks (Mantua and Simonelli, 2019); in addition, the relationship between sleep, cognitive deficit, and the prevalence of AD has been confirmed by a meta-analysis (Bubu et al, 2017). A study of nearly 8,000 people found that those who consistently got 6 h of sleep or less per night during 25 years from their 50 s to 60 s were 30 percent more likely to develop dementia later in life, compared with those who slept 7 h per night (Sabia et al, 2021).…”
Section: The Cognitive Cost Of Sleep Restrictionmentioning
confidence: 93%